Online Nutrition Algorithm For Hemodialysis Patients Improves Dietitian-Patient Interactions - Rosa Hand; Janeen Leon; Lilian Cuppari; Alison Steiber (The Korean Society of Nephrology, 2012)
The purpose of this study was to determine the usability of an online nutrition algorithm for hemodialysis patients by surveying a group of dietitians testing the algorithm. Subjects were invited to take 2 different online surveys, one at month 3 (n=22) and one at month 6 (n=14). JMP version 9.0.2 was used for analysis and significance was set at p<0.05. There was a 73% response rate for survey 1 with a mean of 8.5±4.5 patient visits using the algorithm (range 0-16). Forty-five percent of respondents were from the US, and 55% worked in a chain-based outpatient dialysis facility. Seventy-two percent reported that it was harder than expected to use the algorithm, with half mentioning the time to enter data as a main difficulty. One dietitian used a computer directly at chair-side; 41% thought that using a computer at chair-side would make the process easier or much easier, while 36% thought it would be harder or much harder. Fifty percent thought using the algorithm improved their patient interactions while 41% saw no change. Thirty-six percent felt the algorithm was logical and/or easy and 36% were neutral. Dietitians more experienced with the algorithm were more likely to rate it as logical (ns). There was a 100% response rate in the second survey. Respondents worked at chain-based outpatient facilities in the USA, and all had used the algorithm for 6 months on 2-4 patients. Sixty-four percent of respondents felt the algorithm improved or significantly improved their patient interactions, the remainder saw no change, and 57% thought the algorithm increased their understanding of the patient's condition. Algorithm use increased the mean estimated monthly nutrition care time per patient compared to average habits (p<0.001); 45±27 minutes without the algorithm,100±43 minutes in month 1 of the algorithm, and 77±35 minutes in the last month. The additional time was distributed evenly between interaction and documentation. These surveys show that dietitians felt that an online nutrition algorithm may improve dietitian-patient interactions and understanding of patient conditions which may be helpful in medically complex cases.